Comparing Clinical Outcomes of Five-Strand Hamstring Tendon Autograft and Quadrupled Hamstring Tendon Autograft for Single Bundle Anterior Cruciate Ligament Reconstruction in Filipinos: An Ambi-directional Cohort Study - Villegas, Albert Ian; Mata, Emmanuel Roy; San Juan, Jose Antonio; Go, John Rey; Ladica, Vick Roland (Philippine Journal of Orthopaedics, 2025)
Background. Anterior cruciate ligament (ACL) tears are common, especially in athletes, and are often treated with hamstring tendon autografts using a single-bundle technique. Graft diameter is crucial, with evidence showing that larger grafts reduce failure risk. Asian populations typically have smaller graft diameters. This study compares the clinical outcomes of the five-strand versus the quadrupled technique in a Filipino Asian population to assess potential benefits in graft thickness and knee stability. Objective. To compare the functional outcomes, graft sizes, failure rates, and time to return to sports between five-strand and quadrupled hamstring tendon autografts in ACL reconstruction. Methodology. This ambi-directional cohort study involved Asian Filipino patients aged 18–50 with unilateral ACL tears who underwent single-bundle ACL reconstruction with either quadrupled or five-strand hamstring autografts between January 2022 and August 2023. Data on graft dimensions, IKDC scores, and time to return to sports were collected pre- and postoperatively. The analysis included descriptive statistics, Fisher’s exact test, t-tests, and ANOVA, with significance at p <0.05. Results. The study included 18 patients, showing no significant differences in demographic characteristics such as age (24.78 vs. 27.67 years, p = 0.202), height (1.71 vs. 1.64 meters, p = 0.146), weight (84.43 vs. 74.98 kg, p = 0.252) body mass index (28.95 vs. 27.98 kg/m², p = 0.714), or average return to sports (10.63 vs. 11.83 months, p = 0.642). There was no significant difference in thicknesses (p = 0.089) and lengths (p = 0.885) of the graft. IKDC scores showed no significant differences between the two groups in pre- or postoperative outcomes at six months and one year. Complications were minimal, with no significant difference found. Conclusion. Both the five-strand and quadrupled techniques demonstrated similar demographics, graft dimensions, and clinical outcomes, indicating comparable functional results and safety profiles.